The Role of the Nation's Generation in Maintaining the Pancasila Ideology Amid the Onslaught of the Entry of Foreign Cultures into Indonesia - Bayu Nur’Alam; F.G Cempaka Timur Timur (CV. AFDIFAL MAJU BERKAH, 2024)
In light of the current global phenomenon, Indonesia is welcoming an increasing number of foreign cultures with ease. This can't be denied alongside the advancement of the inexorably fast globalization time and mechanical improvements that are progressively assisting people with having the option to acquire data rpidly and without any problem. Although it isnot against the law for foreign cultures to enter Indonesia, there are still a lot of Indonesians who are unable to distinguish between these cultures. This leang ds to a decline in nationalism values and a fear of a shift in national ideology, such as Pancasila, which is influencedby foreign cultures. has the potential to jeopardize the existence of the state and nation. The more youthful age is one of the variables that is enormously impacted by the section of this unfamiliar culture assuming it is inappropriate to answer and channel the approaching unfamiliar culture. There are currently a number of distinct generations of young people, beginning with generation X, also known as Millennials, and generation Z, each of which possesses its own set of characteristics. In this case there is a concern that there will be changes and shifts in culture and ideology with the influence of foreign culture and ideology entering Indonesia in the midst of the industrial revolution 4.0 which can threaten the sovereignty and existence of ideologies that are embedded in the Indonesian generation. This study uses qualitative research methods with the aim of seeing the character of each generation of the nation to be able to see and accept the impact of foreign cultural and ideological influences that enter Indonesia which will later have an impact on how to overcome and anticipate shifts in the nation's ideology, namely Pancasila from foreign cultural influences and external ideology that can threaten the sovereignty of Pancasila ideology.